Harnessing the Public Health Power of Model Codes to Increase Drinking Water Access in Schools and Childcare. Issue 1 (March 2015) - Wilking, Cara L.; Cradock, Angie L.; Gortmaker, Steven L.
<x xml:space="preserve">Abstract</x> Drinking water infrastructure in schools and childcare is shaped by state and local plumbing codes that are derived from model codes set by private organizations. This article describes the model code process and policy intervention points where the public health community can work to improve child drinking water access.